6-Acetyl-2,2-Dimethylchroman-4-One Isolated from Artemisia princeps Suppresses Adipogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stromal Cells via Activation of AMPK - Karadeniz, Fatih; Oh, Jung Hwan; Lee, Jung Im; Kim, Hojun; Seo, Youngwan; Kong, Chang-Suk (Journal of medicinal food, 2020)
Obesity is a world-wide health concern with increasing mortality and morbidity rates. Development of novel therapeutic agents for obesity from phytochemicals may lead to the effective prevention and control of obesity and obesity-related complications. 6-acetyl-2,2-dimethylchroman-4-one ( ) was isolated from a dietary plant, . The antiobesity effect of compound was determined in human bone marrow-derived mesenchymal stromal cells (hBM-MSCs) induced to differentiate into adipocytes. Treatment with compound resulted in decreased lipid accumulation and expression of key adipogenic markers, proliferator-activated receptor- , CCAAT/enhancer-binding protein- , and sterol regulatory element-binding transcription factor 1. It was also shown that compound downregulated the adipogenesis-induced p38 and JNK MAPK activation, while upregulating adipogenesis inhibitory -catenin-dependent Wnt10b pathway. Compound was also able to stimulate adenosine monophosphate-activated protein kinase phosphorylation, which was suggested to be the underlying mechanism that resulted in inhibition of adipogenesis in hBM-MSCs. In conclusion, 6-acetyl-2,2-dimethylchroman-4-one was identified as a bioactive constituent of that exerts antiobesity properties suppressing adipocyte formation.